Prescribing pattern of dipeptidyl peptidase 4 inhibitors and level of HBA1C target achievements among outpatients with type 2 diabetes mellitus in a Malaysian university teaching hospital - Elnaem, Mohamed Hassan Abdelaziz; Shamsuri, Mohamad Hafiz Hakeem; Mohamad Aziz, Nur Athirah; Alias, Nurul Iman; Hafizi, Rauha Farhana; Latif, Nur Faezah; Rashid, Arina Norhazwani; Mohamad Jalil, Mohd Faris Aiman; Wei Ying, Mery Hu (Walter de Gruyter, 2020)
Background and aims: Oral antidiabetic drugs, including Dipeptidyl Peptidase 4 Inhibitors (DPP4i), are the mainstay for therapeutic management of type 2 diabetes mellitus (T2DM). We aimed to describe the prescribing pattern of DPP4i agents and to assess the achievement of the target HbA1c levels among current DPP4i users at a Malaysian University teaching hospital. Material and method: A retrospective cross-sectional study was conducted in the outpatient diabetes clinic of a university teaching hospital in Pahang, Malaysia. The data included adults with T2DM who received DPP4i prescriptions at least three months before December 2019 and reported data of HbA1c after at least three months from the index date. Evaluation of the DPP4i prescribing patterns referred to the national clinical practice guidelines. Results: 140 cases were included. Sitagliptin 50 mg is the most commonly prescribed DPP4i regimen (72.1%), and its combination therapy with metformin contributed to 67.1% of the total DPP4i prescriptions. About 35% of patients achieved their target HbA1c levels after at least three months on DPP-4 inhibitors therapy. There was no significant association between the type of DPP4i and the target HbA1c achievement (p=0.205). Conclusions: DPP4i medications were more prescribed as combination therapy with metformin, compared to monotherapy except for vildagliptin. Gliclazide was the most common co-prescribed OAD with vildagliptin. Barriers to achieving optimal glycemic control for patients on OAD, particularly DPP4i, need further investigations.